2016
DOI: 10.1111/jgs.14030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potentially Inappropriate Use of Antimuscarinic Medications on Healthcare Use and Cost in Individuals with Overactive Bladder

Abstract: Potentially inappropriate medication use was highly prevalent and was associated with greater total healthcare costs. Providers should carefully consider medical history and concurrent medication use when initiating antimuscarinic medication for the treatment of OAB. Development of interventions to reduce potentially inappropriate use of antimuscarinics in individuals with OAB is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…Anticholinergic burden arising from an accumulation of medicines with anticholinergic properties is associated with an increased risk of cardiovascular disease, mortality and use of healthcare services (Myint et al 2015, Campbell et al 2016. In one US study, one third of anticholinergic prescriptions were found to be potentially inappropriate, and this was associated with increased hospitalisation (Suehs et al 2016). Caution is recommended regarding the prescription of anticholinergics for incontinence in older people and they should be avoided in those with dementia (O'Mahony et al 2015).…”
Section: Anticholinergicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticholinergic burden arising from an accumulation of medicines with anticholinergic properties is associated with an increased risk of cardiovascular disease, mortality and use of healthcare services (Myint et al 2015, Campbell et al 2016. In one US study, one third of anticholinergic prescriptions were found to be potentially inappropriate, and this was associated with increased hospitalisation (Suehs et al 2016). Caution is recommended regarding the prescription of anticholinergics for incontinence in older people and they should be avoided in those with dementia (O'Mahony et al 2015).…”
Section: Anticholinergicsmentioning
confidence: 99%
“…In 2017, almost £148 million was spent on seven million prescriptions for anticholinergics in England (NHS Digital 2018), and consequently these are relatively expensive medicines (Samuelsson et al 2015, Moyson et al 2017. Because of their potential for significant harm, high cost and limited efficacy, the identification of approaches to discontinue anticholinergics is recommended (Suehs et al 2016). One randomised controlled trial of patients receiving anticholinergics for more than six months found that these could be successfully discontinued in 35% of patients (Lee et al 2011).…”
Section: Anticholinergicsmentioning
confidence: 99%
“…Beers, Screening Tool of Older Persons Prescriptions) and judgement‐based measures such as the Medication Appropriateness Index which asks a series of questions about the appropriateness of the drug in question. These drugs are considered inappropriate because older adults who use PIMs are more likely to experience adverse drug reactions, falls, hospitalization and increased healthcare costs …”
Section: Introductionmentioning
confidence: 99%
“…One study found that anticholinergic prevalence among older adults with dementia was 23% [30]. Another found that 31% of Medicare Advantage Prescription Drug Plan members who were newly initiated on a bladder antimuscarinic had a drug-drug or drug-disease interaction; dementia was the most common such interaction, present in 11% of people initiated on a bladder antimuscarinic drug [17]. Previous research has shown that multiple anticholinergic drugs are often prescribed concurrently, causing anticholinergic side effects to accumulate [31,32], and that bladder antimuscarinic use is common in individuals receiving ChEIs for treatment of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the concern about anticholinergic side effects, bladder antimuscarinics may be involved in adverse drug-drug interactions [17]. For example, because bladder antimuscarinics work by blocking the activity of acetylcholine at muscarinic receptors, they may directly counteract the already-modest therapeutic effect of cholinesterase inhibitors (ChEIs), one of two US Food and Drug Administration (FDA)-approved pharmacotherapies for dementia [18].…”
Section: Introductionmentioning
confidence: 99%